Effects of a forming process on the properties and structure of RANEY®-Ni catalysts for the hydrogenation of 1, 4-butenediol. Issue 10 (5th February 2020) - Gao, Xianlong; Mo, Wenlong; Ma, Fengyun; Noritatsu, Tsubaki; Wu, Hongli; Fan, Xing
Abstract : Xianlong Gao's paper focuses on the effects of a forming process on the catalytic hydrogenation of 1, 4-butenediol (BED) to produce 1, 4-butanediol (BDO). The evaluation results showed that the RNAA catalyst showed excellent hydrogenation performance. Abstract : Three commercial Ni–Al alloys formed by a vacuum atomization method (NAV), atmospheric atomization method (NAA) and high-temperature melting method (NAH) were leached by 10 wt% NaOH solution to prepare three RANEY®-Ni catalysts (RNAV, RNAA and RNAH, correspondingly). The effects of a forming process on the structure of Ni–Al alloys and the corresponding RANEY®-Ni catalysts were investigated via XRD, XPS, SEM, TEM, NH3 -TPD, N2 adsorption–desorption and EDX-mapping studies. Also, the as-prepared RANEY®-Ni catalysts were evaluated via the hydrogenation of 1, 4-butenediol (BED) to produce 1, 4-butanediol (BDO). The results showed that the specific surface areas and surface morphologies of the Ni–Al alloys present significant differences. Meanwhile, the RNAA sample presented a comparatively regular morphology, similar to a small piece of sugar cane. The weak and medium acid peak areas of the RNAA catalyst were lower than those of the other samples. RNAV showed higher weak and medium acid peak areas, demonstrating the higher number of acid centers on the surface of the catalyst. The surface of the RNAA catalyst obtained from NAA contained more active component-Ni, about 90 wt% on the surface, and the specific surface area of the sample was 75 times that of its precursor Ni–Al alloy powder (NAA). The evaluation results present that the RNAA catalyst shows better hydrogenation performance, with BED conversion of 100%, both BDO selectivity and yield of 46.11%.